Infection with Cryptosporidium parvum Affects Secondary Sexual Characteristics of Male Mice by Altering the Pheromone Content in Preputial Gland - Gaojian Li; Tao Zhang; Bin Hu; Shuyi Han; Chen Xiang; Guohui Yuan; Hongxuan He (Animals, 2023)
The olfactory acuity of female mice allows them to discriminate the urinary odors of males. Parasitic infection can reduce the odor attractiveness of male mice to females and result in female aversion or avoidance responses in odor selection. However, the chemical signaling changes in the pheromone contents produced by the foreskin gland were not fully revealed after parasitic infection. Cryptosporidium parvum (C. parvum) is a common zoonotic intestinal parasite and has a wide range of hosts, including human, domestic animals, and wild animals. In this study, we immunosuppressed ICR/CD-1 male mice by dexamethasone sodium phosphate treatment. After C. parvum infection, physiological indexes such as body weight and organ weight were significantly decreased. Furthermore, the gene expression level of MUP (major urinary protein) in liver and urine were significantly down-regulated, which could be the reason for the decrease in urine attractiveness to females. GC-MS was performed to analyze the changes in the pheromone produced by the preputial gland before and after parasitic infection, and the results indicated that the levels of different pheromones were significantly reduced after parasitic infection. In summary, this study reveals that C. parvum infection damages the secondary sexual characteristics of male ICR/CD-1 male mice and decreases the pheromone content produced by the foreskin gland.